Effect of rice variety and reaction parameters on synthesis and antibacterial activity of silver nanoparticles - Temsiri Suwan (2018)
In the present study, three different rice varieties; Jasmine (JM), Niaw Koko-6 (NKK), and Saohai (SH) were determined for reducing power using ferric reducing antioxidant power (FRAP) assay. SH showed the highest reducing property followed by JM and NKK, respectively. All modified rice samples were used to fabricate silver nanoparticles (AgNPs) by reducing silver nitrate (AgNO3) to metallic Ag. The obtained AgNPs from JM, NKK, and SH namely JM-AgNPs, NKK-AgNPs, and SH-AgNPs, respectively, showed maximum absorption at 410, 408, and 409 nm, respectively, which confirmed the spectra of AgNPs. Reaction parameters such as AgNO3 and modified rice concentration as well as the reaction period were investigated. It was found that increasing of these parameters gave better AgNPs until the concentration of modified rice and AgNO3 reached to 0.3% and 10 mM, respectively and the reaction period reached to 60 min, the most suitable AgNPs were obtained. Among the three rice varieties, SH showed the most potential for synthesis of AgNPs. SH-AgNPs showed the smallest size of 80.4 ± 2.8 nm and the highest zeta potential of - 45.9 ± 1.4 mV. The AgNPs obtained from all three rice varieties showed effective against Escherichia coli than Staphylococcus aureus and SH-AgNPs showed significantly higher antibacterial activity than JM- AgNPs and NKK-AgNPs.